Bioactive compounds of Crocus sativus L. and their semi-synthetic derivatives as promising anti-Helicobacter pylori, anti-malarial and anti-leishmanial agents. (2nd November 2015) - De Monte, Celeste; Bizzarri, Bruna; Gidaro, Maria Concetta; Carradori, Simone; Mollica, Adriano; Luisi, Grazia; Granese, Arianna; Alcaro, Stefano; Costa, Giosuè; Basilico, Nicoletta; Parapini, Silvia; Scaltrito, Maria Maddalena; et al.
Abstract: Crocus sativus L. is known in herbal medicine for the various pharmacological effects of its components, but no data are found in literature about its biological properties toward Helicobacter pylori, Plasmodium spp . and Leishmania spp. In this work, the potential anti-bacterial and anti-parasitic effects of crocin and safranal, two important bioactive components in C. sativus, were explored, and also some semi-synthetic derivatives of safranal were tested in order to establish which modifications in the chemical structure could improve the biological activity. According to our promising results, we virtually screened our compounds by means of molecular modeling studies against the main H. pylori enzymes in order to unravel their putative mechanism of action.